2013
DOI: 10.1063/1.4802955
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature and high responsivity short wavelength II-VI quantum well infrared photodetector

Abstract: We report the experimental demonstration of a room temperature, high responsivity, short wavelength II-VI Zn0.51Cd0.49Se/Zn0.29Cd0.26Mg0.45Se based quantum well infrared photodetector operating between 3 and 5 μm. Spectral response was observed up to room temperature with a cut off wavelength of 5 μm at 280 K. Measurements with a calibrated blackbody source yielded a peak responsivity of over 30 A/W at 280 K and an applied bias of −3 V. The dark current limited peak detectivity at 80 K and 280 K were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In particular, Zn-based II-VI semiconductors (ZnO, ZnS, ZnSe, and ZnTe) are studied for solar cell buffer layers and transparent electrodes [1]. Furthermore, optical bandgap engineering is required for liquid crystal displays (LCDs) and light emitting diodes (LEDs) [2]. Alloys of Zn-based II-VI semiconductors have been studied to investigate bandgap engineering possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Zn-based II-VI semiconductors (ZnO, ZnS, ZnSe, and ZnTe) are studied for solar cell buffer layers and transparent electrodes [1]. Furthermore, optical bandgap engineering is required for liquid crystal displays (LCDs) and light emitting diodes (LEDs) [2]. Alloys of Zn-based II-VI semiconductors have been studied to investigate bandgap engineering possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that selenide-based wide band gap II-VI semiconductors are attractive alternatives for intersubband (ISB) devices, especially those working in the short wavelength range [13][14][15][16]. We have demonstrated that QWIPs with high performance can also be fabricated from ZnCdSe/ZnCdMgSe multiple quantum wells (MQWs) [17][18][19]. ZnCdMgSe can be grown lattice-matched on InP substrates with a large tuneable band gap (from 2.1 to 3.5 eV).…”
Section: Introductionmentioning
confidence: 97%
“…QDIPs were usually fabricated using self-assembled QDs made from III-V based material systems. Instead, in the last few years, II-VI ZnSe based material systems have been comprehensively studied for their possible use in infrared detection [6][7][8].…”
Section: Introductionmentioning
confidence: 99%